2022
DOI: 10.1111/1744-7917.13088
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile socio‐sexual experience determines lifetime sperm expenditure and adult survival in a polygamous moth, Ephestia kuehniella

Abstract: Male animals often adjust their sperm investment in response to sperm competition environment. To date, only a few studies have investigated how juvenile sociosexual settings affect sperm production before adulthood and sperm allocation during the first mating. Yet, it is unclear whether juvenile sociosexual experience (1) determines lifetime sperm production and allocation in any animal species; (2) alters the eupyrene : apyrene sperm ratio in lifetime ejaculates of any lepidopteran insects, and (3) influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…For each treatment, lines between boxes with "*" and "ns" indicate significantly different (P < 0.05) and not significantly different (P > 0.05), respectively. (Liu et al, 2022) and in lifetime ejaculates (Liu et al, 2023) in E. kuehniella. However, our current study indicates that the higher sperm production during the juvenile stage in response to adult males (Fig.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…For each treatment, lines between boxes with "*" and "ns" indicate significantly different (P < 0.05) and not significantly different (P > 0.05), respectively. (Liu et al, 2022) and in lifetime ejaculates (Liu et al, 2023) in E. kuehniella. However, our current study indicates that the higher sperm production during the juvenile stage in response to adult males (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…5). These findings suggest that (1) the number of spermatogonia for producing eupyrenes may be limited (Witalis & Godula, 1993; Jarrige et al, 2015;Mari et al, 2018) so that the adults cannot manufacture more eupyrenes if their juveniles have used most or all of them, and (2) the number of cells for producing apyrenes may be less limited (Silberglied et al, 1984;Cook & Gage, 1995;Liu et al, 2023), allowing adults to produce more apyrene throughout their life regardless of their larval experience. Production of more apyrenes throughout lifetime may be important to gain advantages in sperm competition and fertilization success (Cook & Wedell, 1999;Holman & Snook, 2008;Wedell et al, 2009;Sakai et al, 2019;Hague et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Environmental factors and the nature of these experiences can result in both positive and adverse outcomes (Baroncelli et al., 2010). For instance, studies have indicated that social environments during adolescence influence reproductive aspects in the Mediterranean flour moth ( Ephestia kuehniella ; Liu et al., 2022), and adverse experiences have been linked to altered emotional reactivity in rhesus macaques ( Macaca mulatta ; Howell et al., 2014). Understanding the underlying mechanisms of these experiences is crucial for developing interventions that promote healthy development and overall well‐being in animals.…”
Section: Introductionmentioning
confidence: 99%